Alunos em situação de dificuldades de aprendizagem matemática : diagnóstico e encaminhamento para o laboratório de aprendizagem - Silva, Renata Aparecida da (2022)
In this research, we present as an object of study the diagnosis and referral of students from the 3rd year of Elementary School in a situation of mathematical learning difficulties (DAM) to the Learning Laboratory. We seek to investigate whether the diagnosis and referral of students in the 3rd year of Elementary School in a situation of mathematical learning difficulties (DAM), through a protocol form to the Learning Laboratory, can contribute to the articulating teacher in the development of pedagogical practices that help the student to overcome the difficulties he presents. We designed as the objective of this research to elaborate a diagnostic form/referral protocol to the Learning Laboratory pointing out the difficulties of mathematical learning and, at the same time, the possibility of the form contributing to the overcoming of these difficulties. The methodological choices followed the principles of the qualitative approach of interpretive analysis. Regarding the categories of data analysis, we considered the Traditional and Constructivist approaches. The research context was established in two state schools in Juara-MT, anonymously named Escola Girassol and Escola Lótus. The research subjects were school directors, pedagogical coordinators; regent teachers of the 3rd year of Elementary School and learning articulating teachers. From this context, we carried out the elaboration and development of the technicaltechnological product called Protocol SDAM (Protocol for diagnosis and referral of students in Situation of Mathematical Learning Difficulties), composed of: SDAM form, Acquired Skills Monitoring form (FAHA) and the Dependency Relationship Framework between Skills, prepared by SEDUC-MT (2018). The purpose of the SDAM Protocol is to produce a diagnostic protocol that helps teachers (regent and articulator) in the referral and care of students in the 3rd year of Elementary School in situations of difficulties/lags in mathematical learning. The validation of the SDAM Protocol took place in three specific moments: First, with the group of research collaborators (mathematics teacher, a CEFAPRO training teacher and a psychologist); second - PPGECM's “Research Seminar II”, whose focus is on the presentation and socialization of the Technical-Technological Product to an Evaluation Board, made up of 6 (six) professors: 1 supervisor; 3 (three) teachers from a Basic Education institution; and 2 (two) PhD professors from UFMT and third moment with the regents and articulating professors of the 3rd year of Elementary School. After analysis, we can infer that the SDAM Protocol will serve as an instrument for recording, monitoring and planning, to overcome the difficulties of mathematical learning in the Learning Laboratory. The research analyzes point to the need to understand the difficulties of mathematical learning, related to pedagogical difficulties: teaching (teacher) and learning (student), pedagogical implications in mathematics teaching, learning theories and diagnosis and referral, therefore, the data show us that the referrals of students in situations of difficulties in mathematical learning to the Learning Laboratory are carried out in a generic way. Therefore, the research results make room for future projections, both for the field of pedagogical practices and teacher training and for other research that permeates the area of mathematics teaching.